The Constitutive Androstane Receptor Is an Anti-obesity Nuclear Receptor That Improves Insulin Sensitivity - Gao, Jie; He, Jinhan; Zhai, Yonggong; Wada, Taira; Xie, Wen (The Journal of biological chemistry, 2009)
Obesity and type 2 diabetes are related metabolic disorders of high prevalence. The constitutive androstane receptor (CAR) was initially characterized as a xenobiotic receptor regulating the responses of mammals to xenotoxicants. In this study, we have uncovered an unexpected role of CAR in preventing obesity and alleviating type 2 diabetes. Using a high fat diet (HFD)-induced obesity model, we showed that treatment of wild type mice with the CAR agonist 1,4-bis[2-(3,5 dichloropyridyloxy)] benzene (TCPOBOP) efficiently prevented obesity from happening or reversed preinduced obesity. Treatment with TCPOBOP improved insulin sensitivity in both the HFD-induced type 2 diabetic model and the ob/ob mice. In contrast, CAR null mice maintained on a chow diet showed spontaneous insulin insensitivity, which cannot be relieved by TOPOBOP treatment. The hepatic steatosis in HFD-treated mice and ob/ob mice was markedly reduced by the TCPOBOP treatment. The metabolic benefits of CAR activation may have resulted from the combined effect of inhibition of lipogenesis, very low density lipoprotein secretion and export of triglycerides, and gluconeogenesis as well as increases in brown adipose tissue energy expenditure and peripheral fat mobilization. Moreover, the skeletal muscle of CAR-activated mice showed a decreased incomplete oxidation, despite having a lower expression level of peroxisome proliferator-activated receptor α and its target genes involved in fatty acid oxidation. In summary, our results have revealed an important metabolic function of CAR and may establish this “xenobiotic receptor” as a novel therapeutic target for the prevention and treatment of obesity and type 2 diabetes.